Vipassana Meditation: How It Impacts Communication Skills with Special Reference to Personal, Educational, and Professional Domains - Shukla, Mahabir; Mehta, Charu; Nathani, Neeru (Journal of Neonatal Surgery, 2025)
This research paper provides a comprehensive examination of Vipassana meditation and its profound impact on communication skills across personal, educational, and professional domains. Vipassana, meaning "to see things as they really are," is an ancient Indian meditation technique rediscovered by Gautama Buddha over 2,500 years ago and revived in modern times by S.N. Goenka. Through systematic self-observation, practitioners develop fundamental qualities like self-awareness, emotional regulation, and empathy, and equanimity to effective communication. This paper synthesizes empirical research from neuroscience, organizational behavior, and educational studies to demonstrate how regular Vipassana practice enhances active listening, reduces reactive communication patterns, improves compassionate dialogue and intra and inter personal relationships. This paper concludes with recommendations for integrating Vipassana-based mindfulness practices into communication training programs across various institutional settings.